Pharmacological Preconditioning Using Diazoxide Regulates Store-Operated Ca2 + Channels in Adult Rat Cardiomyocytes - Sampieri, Raúl; Fuentes, Eridani; Carrillo, Elba D.; Hernández, Ascención; García, María C.; Sánchez, Jorge A. (Frontiers in Physiology, 2020)
Voltage-dependent Ca2+ channels and store-operated Ca2+ channels (SOCs) are the major routes of Ca2+ entry into mammalian cells. Previously, we reported that pharmacological preconditioning (PPC) leads to a decrease in the amplitude of L-type calcium channel current in the heart. In this study, we examined PPC-associated changes in SOC function. We measured adult cardiomyocyte membrane currents using the whole-cell patch-clamp technique, and we evaluated reactive oxygen species (ROS) production and intracellular Ca2+ levels in cardiomyocytes using fluorescent probes. Diazoxide (Dzx) and thapsigargin (Tg) were used to induce PPC and to deplete internal stores of Ca2+, respectively. Ca2+ store depletion generated inward currents with strong rectification, which were suppressed by the SOC blocker GSK-7975-A. These currents were completely abolished by PPC, an effect that could be countered with 5-hydroxydecanoate (5-HD; a selective mitochondrial ATP-sensitive K+ channel blocker), an intracellular mitochondrial energizing solution, or Ni2+ [a blocker of sodium–calcium exchanger (NCX)]. Buffering of ROS and intracellular Ca2+ also prevented PPC effects on SOC currents. Refilling of intracellular stores was largely suppressed by PPC, as determined by measuring intracellular Ca2+ with a fluorescent Ca2+ indicator. These results indicate that influx of Ca2+ through SOCs is inhibited by their ROS and Ca2+-dependent inactivation during PPC and that NCX is a likely source of PPC-inactivating Ca2+. We further showed that NCX associates with Orai1. Down-regulation of SOCs by PPC may play a role in cardioprotection following ischemia–reperfusion.